The Residual Effect of Some Insecticides on Plutella xylostella (L) Larvae in the Greenhouse - Mohamad, Rosli; Chong, Wei Cheong; Ibrahim, Yusof (1980)
The residual effect of five insecticides on Plutella xylostella (L) larvae was measured on Brassica rapa in the laboratory. Acephate was the most persistent and gave at least 80% larval mortality eight days after application. Bendiocarb, Bacillus thuringiensis, and methamidophos gave 50% larval mortality six days after treatment. Di[lubenzuron demonstrated poor insecticidal activity - the larval mortality was 20% at all times